ECLAC in its historical setting - Tulio Halperin (CEPAL Review, 2008)
This lecture discusses the features of the colonial situation in Latin America that conditioned the region’s economic and social performance in the nineteenth and early twentieth centuries. It deals in particular with Argentina, looking at the events following the First World War through to the beginning of the Second World War. Those events were formative in the education and experience of Raúl Prebisch, who 30 years later would give ECLAC its fundamental characteristics. The lecture examines the ideas that ECLAC contributed to the debate on Latin American development and the evolution of the countries that applied those ideas. It also looks at the external and internal circumstances that changed the context in which development policies were implemented from the middle of the 1970s onwards. Lastly, it identifies the most recent changes in the world economic situation, and the role of ECLAC in defending the ideas of freedom, well-being and tolerance, which are the essence of modern civilization.